Molecular mechanism of thiazolidinedione-mediated inhibitory effects on osteoclastogenesis. - Dongfeng Zhao (Public Library of Science (PLoS), 2014)
Thiazolidinediones are synthetic peroxisome proliferator-activated receptor γ agonists used to treat type 2 diabetes mellitus. Clinical evidence indicates that thiazolidinediones increase fracture risks in type 2 diabetes mellitus patients, but the mechanism by which thiazolidinediones augment fracture risks is not fully understood. Several groups recently demonstrated that thiazolidinediones stimulate osteoclast formation, thus proposing that thiazolidinediones induce bone loss in part by prompting osteoclastogenesis. However, numerous other studies showed that thiazolidinediones inhibit osteoclast formation. Moreover, the molecular mechanism by which thiazolidinediones modulate osteoclastogenesis is not fully understood. Here we independently address the role of thiazolidinediones in osteoclastogenesis in vitro and furthermore investigate the molecular mechanism underlying the in vitro effects of thiazolidinediones on osteoclastogenesis. Our in vitro data indicate that thiazolidinediones dose-dependently inhibit osteoclastogenesis from bone marrow macrophages, but the inhibitory effect is considerably reduced when bone marrow macrophages are pretreated with RANKL. In vitro mechanistic studies reveal that thiazolidinediones inhibit osteoclastogenesis not by impairing RANKL-induced activation of the NF-κB, JNK, p38 and ERK pathways in bone marrow macrophages. Nonetheless, thiazolidinediones inhibit osteoclastogenesis by suppressing RANKL-induced expression of NFATc1 and c-Fos, two key transcriptional regulators of osteoclastogenesis, in bone marrow macrophages. In addition, thiazolidinediones inhibit the RANKL-induced expression of osteoclast genes encoding matrix metalloproteinase 9, cathepsin K, tartrate-resistant acid phosphatase and carbonic anhydrase II in bone marrow macrophages. However, the ability of thiazolidinediones to inhibit the expression of NFATc1, c-Fos and the four osteoclast genes is notably weakened in RANKL-pretreated bone marrow macrophages. These in vitro studies have not only independently demonstrated that thiazolidinediones exert inhibitory effects on osteoclastogenesis but have also revealed crucial new insights into the molecular mechanism by which thiazolidinediones inhibit osteoclastogenesis.